2001
DOI: 10.1074/jbc.c100171200
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophin Receptor-interacting Mage Homologue Is an Inducible Inhibitor of Apoptosis Protein-interacting Protein That Augments Cell Death

Abstract: The inhibitor of apoptosis proteins (IAPs) have been shown to interact with a growing number of intracellular proteins and pathways to fulfil their anti-apoptotic role. In the search for novel IAP-interacting proteins we identified the neurotrophin receptor-interacting MAGE homologue (NRAGE) as being able to bind to the avian IAP homologue ITA. This interaction requires the RING domain of ITA. NRAGE additionally coimmunoprecipitates with XIAP. When overexpressed in 32D cells NRAGE augments interleukin-3 withdr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 29 publications
2
50
0
Order By: Relevance
“…It interacts with p75NTR to induce NGF-dependent apoptosis (18), and subsequent studies identified two different mechanisms underlying NRAGE-mediated apoptosis. One is by promoting the degradation of the survival protein XIAP (X-linked inhibitor of apoptosis) (19), and the second is by activating the c-Jun N-terminal kinase and caspase signaling pathway, both of which are known signaling cascades for programmed cell death (20). It is not known whether these two mechanisms operate independently, perhaps in different cell types, or whether NRAGE can induce multiple signals to ensure the demise of the cell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It interacts with p75NTR to induce NGF-dependent apoptosis (18), and subsequent studies identified two different mechanisms underlying NRAGE-mediated apoptosis. One is by promoting the degradation of the survival protein XIAP (X-linked inhibitor of apoptosis) (19), and the second is by activating the c-Jun N-terminal kinase and caspase signaling pathway, both of which are known signaling cascades for programmed cell death (20). It is not known whether these two mechanisms operate independently, perhaps in different cell types, or whether NRAGE can induce multiple signals to ensure the demise of the cell.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, it was found to utilize two mechanisms to induce apoptosis in cells. One involves NRAGE-dependent degradation of the survival protein XIAP (X-linked inhibitor of apoptosis) (19) and the other involves NRAGE-dependent activation of the c-Jun N-terminal kinase signaling pathway and caspases (20).…”
mentioning
confidence: 99%
“…A likely candidate for this regulation is the PI3-kinase-Akt pathway, which comprises the major NGF-mediated survival pathway in these neurons . This pathway has been previously shown to directly regulate the level and activation state of the Bcl-2 family (Datta et al, 1997) and to regulate levels of the IAPs (inhibitor of apoptosis) (Wiese et al, 1999;Jordan et al, 2001), thereby providing multiple checkpoints at different levels to ensure that neurons are only eliminated when they have failed to compete successfully for this trophic factor during the period of naturally occurring neuronal death.…”
Section: Discussionmentioning
confidence: 99%
“…NRAGE is a p75 NTR-binding protein (46) that regulates cell cycle progression and promotes apoptosis by enhancing the apoptotic effect of the p75 NTR (47,48). NRAGE also interacts with the Msx and Dlx families of homeodomain proteins that are involved in craniofacial, limb, and nervous system development (49).…”
Section: Discussionmentioning
confidence: 99%